Synthesis of hierarchical 4H/fcc Ru nanotubes for highly efficient hydrogen evolution in alkaline media - Lu, Qipeng (2020)
Hierarchical metal nanostructures containing 1D nanobuilding blocks have stimulated great interest due to their abundant active sites for catalysis. Herein, hierarchical 4H/face-centered cubic (fcc) Ru nanotubes (NTs) are synthesized by a hard template-mediated method, in which 4H/fcc Au nanowires (NWs) serve as sacrificial templates which are then etched by copper ions (Cu2+ ) in dimethylformamide. The obtained hierarchical 4H/fcc Ru NTs contain ultrathin Ru shells (5-9 atomic layers) and tiny Ru nanorods with length of 4.2 ± 1.1 nm and diameter of 2.2 ± 0.5 nm vertically decorated on the surface of Ru shells. As an electrocatalyst for the hydrogen evolution reaction in alkaline media, the hierarchical 4H/fcc Ru NTs exhibit excellent electrocatalytic performance, which is better than 4H/fcc Au-Ru NWs, commercial Pt/C, Ru/C, and most of the reported electrocatalysts.